2016
DOI: 10.1021/acs.est.6b00430
|View full text |Cite
|
Sign up to set email alerts
|

Indications of Transformation Products from Hydraulic Fracturing Additives in Shale-Gas Wastewater

Abstract: Unconventional natural gas development (UNGD) generates large volumes of wastewater, the detailed composition of which must be known for adequate risk assessment and treatment. In particular, transformation products of geogenic compounds and disclosed additives have not been described. This study investigated six Fayetteville Shale wastewater samples for organic composition using a suite of one- and two-dimensional gas chromatographic techniques to capture a broad distribution of chemical structures. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 59 publications
1
128
0
Order By: Relevance
“…Low molecular weight carboxylic acids, in particular, acetate and formate, have been observed in both produced water and effluent from similar fluid-shale experiments (Lee & Neff, 2011, Zhu, et al, 2015, Hoelzer, et al, 2016. The proliferation of these compounds is believed to be related to the labile ester linked carboxyl functional groups attached to the organic matter within the shale formation.…”
Section: Aqueous Organic Chemistrymentioning
confidence: 91%
See 2 more Smart Citations
“…Low molecular weight carboxylic acids, in particular, acetate and formate, have been observed in both produced water and effluent from similar fluid-shale experiments (Lee & Neff, 2011, Zhu, et al, 2015, Hoelzer, et al, 2016. The proliferation of these compounds is believed to be related to the labile ester linked carboxyl functional groups attached to the organic matter within the shale formation.…”
Section: Aqueous Organic Chemistrymentioning
confidence: 91%
“…On average roughly 40% of this fluid returns to the surface upon completion and is then considered produced fluid. Produced fluid has a chemical signature distinctly different from the initially injected HFF (Strong et al, 2014, Hoelzer, et al, 2016, Marcon, et al, 2017 and the copious amounts of fluid generated from thousands of wells drilled within the Marcellus Shale necessitate a better understanding of reactions occurring between HFF and the shale reservoir. Recycling and remediation efforts of produced fluid are of great concern to industry, environmental scientists, and the general public.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Produced water is a waste stream generated along with oil and gas production. This wastewater is often hypersaline and varies in composition during the life of a well and can contain native formation water from oil‐ or gas‐bearing layers, hydraulic fracturing and maintenance chemicals, as well as any reaction byproducts formed via abiotic or biotic processes (Hoelzer et al ; Oetjen et al ; Rosenblum et al ). Nearly 900 billion gallons of produced water are generated each year from current onshore extraction of conventional and unconventional resources in the United States (Veil ).…”
Section: Introductionmentioning
confidence: 99%
“…Limited characterization studies of produced water have identified nearly 600 chemicals in produced water associated with hydraulic fracturing (USEPA ). More recent studies using high‐resolution mass spectrometry indicate that the number of potentially detectable chemicals may be much greater (Hoelzer et al ; Luek and Gonsior ; Luek et al ; Piotrowski et al ).…”
Section: Introductionmentioning
confidence: 99%